2020
DOI: 10.1002/jemt.23606
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological study of the oropharyngeal floor of squabs and adult domestic pigeons (Columba liviadomestica)

Abstract: The current study compared the morphological features of the oropharyngeal floor of squabs and adult domestic pigeons (Columba livia domestica). Samples from the oropharyngeal floor of both squabs and adult pigeons were collected directly after slaughtering. The collected samples were examined grossly, morphometrically, and by scanning electron microscopy (SEM). The lower beak had triangular shape with pointed rostral end. The tongue did not fill the entire oral floor in squabs as well as adult pigeons. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The pharyngeal papillae located on the caudal border of the laryngeal mound is the common structure in all studied developmental age‐stages, similar to that observed in most avian species (Abumandour, 2018; Abumandour & El‐Bakary, 2017a; Abumandour & El‐Bakary, 2017b; Al‐Ahmady Al‐Zahaby, 2016) while, it is completely absent in southern lapwing (Erdogan & Perez, 2015). The presence of the two pharyngeal row were observed in the current work in all developmental stages, that harmonious with previous published articles (Abumandour, 2018; Abumandour & El‐Bakary, 2017a), while, the only one pharyngeal row recorded in some birds (Abumandour & El‐Bakary, 2019a; Abumandour & Gewaily, 2019; Mahdy, 2020), but the three pharyngeal rows observed in the Japanese quail (Madkour, 2018). Functionally, these caudally oriented pharyngeal papillae likely share in orienting the food particles toward the esophagus (Abumandour & El‐Bakary, 2017a; El‐Mansi et al, 2020; Jackowiak & Godynicki, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The pharyngeal papillae located on the caudal border of the laryngeal mound is the common structure in all studied developmental age‐stages, similar to that observed in most avian species (Abumandour, 2018; Abumandour & El‐Bakary, 2017a; Abumandour & El‐Bakary, 2017b; Al‐Ahmady Al‐Zahaby, 2016) while, it is completely absent in southern lapwing (Erdogan & Perez, 2015). The presence of the two pharyngeal row were observed in the current work in all developmental stages, that harmonious with previous published articles (Abumandour, 2018; Abumandour & El‐Bakary, 2017a), while, the only one pharyngeal row recorded in some birds (Abumandour & El‐Bakary, 2019a; Abumandour & Gewaily, 2019; Mahdy, 2020), but the three pharyngeal rows observed in the Japanese quail (Madkour, 2018). Functionally, these caudally oriented pharyngeal papillae likely share in orienting the food particles toward the esophagus (Abumandour & El‐Bakary, 2017a; El‐Mansi et al, 2020; Jackowiak & Godynicki, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The triangular lingual appearance observed in all studied developmental age‐stages considered the common lingual shape in most avian species ( Abumandour, 2018; Abumandour & Gewaily, 2019; Dehkordi et al, 2010; Iwasaki & Kobayashi, 1986; Jackowiak, Skieresz‐Szewczyk, Kwieciński, Trzcielińska‐Lorych, & Godynicki, 2010; Mahdy, 2020; Parchami et al, 2010), while the elongated tongue was observed in some avian species such as house sparrow, common kestrel, Hume's tawny owl, Egyptian laughing dove, Eurasian Coot, white‐tailed eagle, and rock pigeon (Abumandour, 2018; Abumandour & El‐Bakary, 2017a; Abumandour & El‐Bakary, 2017b; Abumandour & El‐Bakary, ; Abumandour & Kandyel, 2020; Jackowiak & Godynicki, 2005). Furthermore, there are other lingual shapes recorded in some avian species that related with their feeding style such as; the oval tongue in Middendorff's bean and Domestic goose (Iwasaki et al, 1997; Jackowiak et al, 2011), the mushroom tongue in cormorants (Jackowiak et al, 2006), Brush tongue in nectarivorous avian species (Rico‐Guevara & Rubega, 2011), toothpick shaped in the Japanese pygmy woodpecker (Emura et al, 2009), and the needle tongue (Emura, 2009), while the rudimental small nonfunctional tongue observed in the Eurasian hoopoe, ratite birds (Abumandour & Gewaily, 2019; Crole & Soley, 2010a; Crole & Soley, 2010b; Jackowiak & Ludwig, 2008; Santos et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(Abumandour & El-Bakary, 2017). Meanwhile, only one pharyngeal papillary row were observed in some birds (Abumandour & Gewaily, 2019;Mahdy, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Some time ago, the avian tongue had more considerations from all scientists by various anatomical methods to its adaptation with the different feeding habits (Abumandour, Shukry, et al, 2021; Abumandour, Farrag, et al, 2021; Al‐Ahmady, 2016; Crole and Soley, 2010b; Jackowiak & Ludwig, 2008b; Kobayashi et al, 1998; Skieresz‐Szewczyk & Jackowiak, 2016). Over time, the anatomical researchers have resorted to investigating the oropharyngeal cavity and its adaptability with the obtainable food particles in different environmental conditions (Abumandour, El‐Bakary, et al, 2021; Abumandour, Farrag, et al, 2021; El‐Mansi et al, 2020; El‐Mansi et al, 2021; Gewaily & Abumandour, 2020; Mahdy, 2020).…”
Section: Introductionmentioning
confidence: 99%